Perlakuan akuntansi industri migas pasca konvergensi psak no.29 terhadap international financial report standar (psak no.33) studi kasus pada PT. Chevron pasific indonesia - Djonathan Kevin Kegen Hutagalung; Kamaliah '; Muhammad Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the effect treatment of accounting of migas after convergence PSAK No.29 for International Financial Report Standard ( PSAK No. 33). Object of this research at PT. Chevron Pasific Indonesia. Method analyse data used in this research use descriptive method, that is compared theory with practice in PT. Chevron Pasific Indonesia.From result of research which have been, PT. Chevron Pasific Indonesia not execute method of Successful Effort purely, because in execution of accounting PT. Chevron Pasific Indonesia also be based on the PSC Accounting. Costs that happened at PT. Chevron Pasific Indonesia identified by three cost, that is: operating expense (OE), capital expenditure budget (CEB) and acquisition cost. In confession to four first cost, acquisition cost, exploration cost, develompent cost and production cost, PT. Chevron Pasific Indonesia in general have used Successful Effort. But, special for treatment to costs which intangible (IDC-Intangible Drilling Cost) PT. Chevron Pasific Indonesia apply Production Sharing Contract. Costs of Intangible at PT. Chevron Pasific Indonesia treated by according to Production Sharing Contract, among other things is: labor, materials and service, auxiliaries and utilities, office service and general administration, production drilling-labor, exploraatory drillinglabor, survey-labor, other exploration expenditure. Based to PSC Accounting, direct acquistion cost fully amortize, but only on footnote, while PSAK acquistion cost of based to age contract.Keyword : Acquisittion Cost, Exploration Cost, Development Cost, Production Cost, Asset Retirement Obligations